Identification Of Sorgum Distribution And Soil Nutrient Status In Local Sorgum Genotype Growing Locations In North Sumatera - Mukhtar Yusuf; Dyah Roestawita; Dafni Mawar Tarigan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Sorghum, a drought-resistant cereal crop, has great potential to support food security in North Sumatra. To optimize its utilization, identification and characterization of local sorghum varieties are needed. Identification of local sorghum plants is an important step in efforts to optimize the utilization of plants that are useful for helping to document and preserve biodiversity, can help reveal hidden potential, so that superior varieties can be developed. Farmers can choose the varieties that best suit their agronomic conditions and needs so that they can help open up new opportunities for product development and downstreaming of sorghum, thereby increasing its economic value. By developing and utilizing local sorghum varieties, Indonesia can reduce dependence on food imports and strengthen its food sovereignty Data collection was carried out from August to December 2022 in several regencies/cities in North Sumatra based on information sources from the agricultural service, farmer groups and communities who know about sorghum cultivation. This study aims to collect soil samples in sorghum plantations in various regions in North Sumatra. The soil nutrients in local sorghum growing locations vary, in terms of soil pH content, almost all locations fall into the acid criteria, the soil N content falls into the low criteria, and the soil P content is very low.